Nutrition Assessment, Counseling, and Support Interventions to Improve Health-Related Outcomes in People Living With HIV/AIDS: A Systematic Review of the Literature. (15th April 2015) - Tang, Alice M.; Quick, Timothy; Chung, Mei; Wanke, Christine A.
Abstract : Background: Although numerous studies have shown that severe to moderate wasting at the time of antiretroviral therapy initiation is strongly predictive of mortality, it remains unclear whether nutritional interventions at or before antiretroviral therapy initiation will improve outcomes. This review examines data on nutrition assessment, counseling, and support interventions in resource-limited settings. Methods: We identified articles published between 2005 and 2014 on the effectiveness of nutrition assessment, counseling, and support interventions, particularly its impact on 5 outcomes: mortality, morbidity, retention in care, quality of life, and/or prevention of ongoing HIV transmission. We rated the overall quality of individual articles and summarized the body of evidence and expected impact for each outcome. Results: Twenty-one articles met all inclusion criteria. The overall quality of evidence was weak, predominantly because of few studies being designed to directly address the question of interest. Only 2 studies were randomized trials with no food support control groups. The remainder were randomized studies of one type of food support versus another, cohort (nonrandomized) studies, or single-arm studies. Ratings of individual study quality ranged from "medium" to "weak, " and the quality of the overall body of evidence ranged from "fair" to "poor." We rated the expected impact on all outcomes as "uncertain." Conclusions: Rigorous better designed studies in resource-limited settings are urgently needed to understand the effectiveness of nutrition assessment and counseling alone, as well as studies to understand better modalities of food support (targeting, timing, composition, form, and duration) to improve both short- and long-term patient retention in care and treatment, and clinical outcomes. Abstract : Supplemental Digital Content is Available in the Text.